2015
DOI: 10.1007/s00705-015-2682-x
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt emergence and predominance in Vietnam of rotavirus A strains possessing a bovine-like G8 on a DS-1-like background

Abstract: An apparently single rotavirus A strain possessing a genotype constellation of G8-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2 abruptly emerged, caused diarrhoea in children requiring hospitalisation, and increased to reach 27 % of strains detected during the first half of 2015 in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 12 publications
3
67
0
Order By: Relevance
“…For example, a high frequency of G8P [6] has been reported in São Tom e and Pr ıncipe in Africa [Istrate et al, 2015]. Recently, DS-1-like G8P[8] strains similar to those in Thailand detected in this study were found in a high proportion (27%) in Vietnam in 2015 [Hoa-Tran et al, 2016].…”
Section: Discussionsupporting
confidence: 59%
“…For example, a high frequency of G8P [6] has been reported in São Tom e and Pr ıncipe in Africa [Istrate et al, 2015]. Recently, DS-1-like G8P[8] strains similar to those in Thailand detected in this study were found in a high proportion (27%) in Vietnam in 2015 [Hoa-Tran et al, 2016].…”
Section: Discussionsupporting
confidence: 59%
“…The genomes of these G8P[8] strains shared >99.6% nt identity with each other (Table 2; Technical Appendix). All 11 genome segments of strain To14-0 (the representative G8P[8] strain in this study) exhibited the highest nucleotide identity to human G8P[8] strains isolated in Southeast Asia in 2014 (represented by strain RVN1149 from Vietnam [>99.4% nt identity] and NP-130 from Thailand [>99.5% nt identity]) ( 6 , 7 ) (Table 2). This finding suggests that the strains share a common G8P[8] origin.…”
Section: The Studymentioning
confidence: 93%
“…Furthermore, in 2013–2014, we identified DS-1-like intergenogroup reassortant strains having G8P[8] genotypes (including strains KKL-17, PCB-79, PCB-84, PCB-85, PCB-103, SKT-107, SWL-12, NP-130, PCB-656, SKT-457, SSKT-269, and SSL-55) in Thailand as major strains [29]. Similar DS-1-like G8P[8] strains (including strain RVN1149) were subsequently detected in Vietnam in 2014–2015 [25]. G8, like G6 and G10, is one of the common G genotypes in cattle that has been identified in humans sporadically [30].…”
Section: Introductionmentioning
confidence: 99%
“…G8, like G6 and G10, is one of the common G genotypes in cattle that has been identified in humans sporadically [30]. Although human G8 strains are particularly prevalent in Africa, they have been infrequently detected elsewhere [25, 31]. In 2015, the emergence of DS-1-like G3P[8] strains (including strains ERN8263 and SS96217158) was recognized in Hungary and Spain, Europe [21, 23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation